1343A systematic review and meta-analysis of tobacco smoking behaviour changes during the COVID-19 pandemic. (2nd September 2021) - Vaneckova, Pavla; Sarich, Peter; Cabasag, Citadel Jungco; Liebermann, Erica; Carle, Chelsea; Hughes, Suzanne; Egger, Sam; O'Connell, Dianne; Weber, Marianne; da Costa, Allini Mafra; Caruana, Michael; Gouda, Hebe; et al.
Abstract: Background: Globally, tobacco smoking remains the largest cause of premature death. The COVID-19 pandemic has forced nations to take unprecedented measures including 'lockdowns' that might impact tobacco smoking behaviour. We performed a systematic review and meta-analyses to assess smoking behaviour changes during the early phases of the COVID-19 pandemic. Methods: We searched Medline/Embase/PsycINFO/BioRxiv/MedRxiv/SSRN databases (January-November 2020) for published and pre-print articles that reported specific smoking behaviour changes or intentions after the onset of the COVID-19 pandemic. We used random-effects models to pool prevalence ratios comparing the prevalence of smokers during and before the pandemic, and the prevalence of smoking behaviour changes. Results: 33 studies were included in meta-analyses, with smoking data for ∼230, 000 participants across 24 countries. The proportions of smokers during and before the pandemic were similar, with a pooled prevalence ratio 0.85 (95%CI:0.76-0.95). In studies limited to smokers,  27% (95%CI:21-32%) smoked more, 17% (95%CI:13-21%) smoked less, 54% (95%CI:47-61%) smoked the same and 5% (95%CI:2-9%) reported quitting smoking. Among all participants, 1% (95%CI:0-2%) started smoking during the pandemic. All studies were at high risk of bias due to use of non-representative samples, likely non-response bias, and utilisation of non-validated questions. Conclusions: Smoking behaviour changes during the early phases of the COVID-19 pandemic were highly mixed. Meta-analyses indicated slightly lower overall smoking prevalence during the pandemic, but higher intensity among smokers. Key messages: More recent and higher quality studies of smoking behaviour changes are required to measure the longer term impact of the COVID-19 pandemic.